Science and engineering careers in the United States : an analysis of markets and employment - Freeman, Richard B. (Richard Barry), 1943-; Goroff, Daniel L. (National Bureau of Economic Research conference report., 2009)
Beginning in the early 2000s, there was an upsurge of national concern over the state of the science and engineering job market that sparked a plethora of studies, commission reports, and a presidential initiative, all stressing the importance of maintaining American competitiveness in these fields. Science and Engineering Careers in the United States is the first major academic study to probe the issues that underlie these concerns. This volume provides new information on the economics of the postgraduate science and engineering job market, addressing such topics as the factors that determine.